Kali macrura ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Kali macrura (Parr, 1933). Longnose Swallower. To 13 cm (5.1 in) SL (Melo 2008). Circumglobal; southern California to Baja California (Johnson and Cohen 1974), and near mouth of Gulf of California (Personal communication: Los Angeles County Museum of Natural History Fish Collection, Los Angeles, California). Mesopelagic and bathypelagic; depth: 600–2,750 m (1,968 –9,020 ft) or deeper (min.: Moore et al. 2003; max.: Melo 2008). Does not occur in the eastern Pacific (Fricke et al. 2020). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 192, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...